PENGEMBANGAN VIDEO ANIMASI BERBASIS PROFIL PELAJAR PANCASILA UNTUK SISWA DI SEKOLAH DASAR - Siti Khadijah; Siti Nur Sucia Ningsih (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study intends to generate animated video media based on the Pancasila Student Profile to increase elementary school students' creative thinking skills. The findings show that the animated video content that was created is very useful and valid for usage in classrooms. According to effectiveness tests, students' engagement and learning outcomes—particularly in creative thinking—are greatly enhanced by the media. The animated video's strength is its adaptability, which allows for self-directed learning and fosters a fun learning environment. As a result, this media works well to assist the Pancasila Student Profile's implementation in primary school.